Numerical modeling of geothermal systems with applications to Krafla, Iceland and Olkaria, Kenya - Bodvarsson, G.S. (Lawrence Berkeley Laboratory, 1987)
The use of numerical models for the evaluation of the generating potential of high temperature geothermal fields has increased rapidly in recent years. In the present paper a unified numerical approach to the modeling of geothermal systems is discussed and the results of recent modeling of the Krafla geothermal field in Iceland and the Olkaria, Kenya, are described. Emphasis is placed on describing the methodology using examples from the two geothermal fields.